Pengembangan Metode Sahl untuk Meningkatkan Pembelajaran Imla Aksara Arab Melayu di Madrasah Diniyah Takmiliyah Kecamatan Siabu - Manahan Efendi; Zulhimma Zulhimma; Zainal Efendi Hasibuan (Intellect : Indonesian Journal of Learning and Technological Innovation, 2025)
The decline of the Arab-Malay academic tradition among students highlights the need for relevant and contextual learning innovations. This study aims to develop a learning model for Arab-Malay script to improve imla (dictation) learning outcomes in Madrasah Diniyah Takmiliyah (MDT) in Siabu District, Mandailing Natal Regency. The research employed the ADDIE development model, which includes the stages of needs analysis, design, development, implementation, and evaluation. The trial was conducted in three MDTs and showed that the developed Sahl method met the criteria of validity, practicality, and effectiveness. Students' learning outcomes improved in most madrasahs, and both teachers and students responded very positively regarding the practicality of the method. These findings indicate that the Sahl method is feasible for use in imla learning at MDTs as an effort to preserve the Arab-Malay cultural heritage. Abstrak Penurunan budaya akademik Arab Melayu di kalangan pelajar mendorong perlunya inovasi pembelajaran yang relevan dan kontekstual. Penelitian ini bertujuan untuk mengembangkan model pembelajaran aksara Arab Melayu guna meningkatkan hasil belajar imla di Madrasah Diniyah Takmiliyah (MDT) Kecamatan Siabu, Kabupaten Mandailing Natal. Metode yang digunakan adalah model pengembangan ADDIE, yang mencakup tahapan analisis kebutuhan, perancangan, pengembangan, implementasi, dan evaluasi. Uji coba dilaksanakan di tiga MDT, dan hasilnya menunjukkan bahwa metode Sahl yang dikembangkan memenuhi kriteria validitas, kepraktisan, dan keefektifan. Terdapat peningkatan hasil belajar siswa di sebagian besar madrasah, dengan respon guru dan siswa yang sangat positif terhadap kepraktisan metode. Temuan ini mengindikasikan bahwa metode Sahl layak diterapkan dalam pembelajaran imla di MDT sebagai upaya pelestarian budaya Arab Melayu.